Method for promoting bone defect repair by using calcined native copper beta-tricalcium phosphate stent
By preparing calcined natural copper/β-tricalcium phosphate scaffolds, using 3D printing frozen casting technology and Notch-VEGF signaling pathway, the problems of insufficient calcined natural copper administration methods and insufficient mechanical properties of ceramic materials in bone defect repair were solved, and the problem of insufficient calcined natural copper administration methods and insufficient mechanical properties of ceramic materials was achieved. Rapid repair and mechanical strength improvement of bone defects.
Patent Information
- Application Number
- CN202411254373.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing bone defect repair technology lacks innovative calcined natural copper delivery methods, and the mechanical properties of traditional ceramic materials are insufficient, making it difficult to effectively promote the repair of bone defects.
By preparing calcined natural copper/β-tricalcium phosphate scaffolds, 3D printing frozen casting technology was used to prepare bone repair scaffolds loaded with traditional Chinese medicine, providing mechanical support, promoting angiogenesis of HUVECs, and upregulating Notch1, VEGF, and BMP2 through the Notch-VEGF signaling pathway The expression of the stochastic-vascular coupling promotes osteogenesis and accelerates bone defect repair.
The method of using calcined natural copper has been broadened, the mechanical strength of the stent has been improved, the mechanical properties of traditional ceramic materials have been improved, and the repair process of bone defects has been significantly accelerated, providing a clinical orthopedic treatment option with good biosafety and physical and chemical properties.
Smart Images

Figure CN119113204A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bone defect repair, and more specifically to a method for promoting bone defect repair by using a calcined natural copper beta-tricalcium phosphate scaffold. Background Art
[0002] Bone defect refers to the shortage of bone caused by trauma or surgery, which is called bone defect; such as comminuted fractures caused by trauma, inflammation, bone disease and other factors, open fractures with large bone tissue defects, bone necrosis and separation caused by inflammation, bone infarction or bone ischemic necrosis caused by large areas of bone necrosis, etc. These are all bone defects caused by diseases. Due to the existence of bone defects, bone non-union, delayed healing or non-healing, and local functional disorders are often caused.
[0003] β-tricalcium phosphate (β-TCP) has good biocompatibility and biodegradability, can provide a certain degree of physiological support for bone cells, and helps promote bone tissue growth. It is often used in clinical practice as a bone repair and bone replacement material.
[0004] Calcined natural copper is a commonly used mineral Chinese medicine in orthopedics, and mainly contains elements such as Fe, Zn, Ca, Mg, etc. Among them, metal elements such as Fe, Zn, Ca, Mg play an important role in the growth and development of bones and the repair of bone defects. Therefore, it is also commonly used in traditional Chinese medicine to treat bone-related diseases such as osteoporosis, fractures and bone defects. Clinically proven, calcined natural copper has good effects of promoting blood circulation and removing blood stasis, repairing tendons and bones, and relieving pain.
[0005] At present, there is no innovative way to administer calcined natural copper, and there is no specific plan or report on preparing a calcined natural copper / β-tricalcium phosphate scaffold with certain biological activity through freeze casting technology for repairing and promoting bone defect repair; therefore, the present invention aims to provide a method for promoting bone defect repair using a calcined natural copper β-tricalcium phosphate scaffold to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a method for promoting bone defect repair by using a calcined natural copper β-tricalcium phosphate scaffold. The present invention prepares a safe and effective calcined natural copper bone repair scaffold, which can be implanted in situ into a load-bearing bone defect site and provide mechanical support, thereby broadening the calcined natural copper drug delivery method. The scaffold has good performances and can promote angiogenesis of HUVECs and then promote osteogenesis. In the process of bone repair, the expression of Notch1 is upregulated through the Notch-VEGF signaling pathway, and the expression of VEGF, BMP2, etc. can be promoted, thereby promoting osteogenesis-angiogenesis coupling in the process of bone defect repair, thereby achieving a therapeutic effect of accelerating bone defect repair.
[0007] The above technical objectives of the present invention are achieved through the following technical solutions: A method for promoting bone defect repair by calcined natural copper β-tricalcium phosphate scaffold, comprising the following steps:
[0008] S1, preparing a calcined natural copper aqueous extract and adding it to β-TCP;
[0009] S2, taking β-TCP added with a quantitative amount of calcined natural copper water extract, and fully mixing the PVA solution, glycerol, and ultrapure water, removing bubbles, and obtaining a uniform slurry;
[0010] S3, using a syringe to quickly add the uniform slurry on a plate tank pre-cooled at -30°C into the stent mold, and after the slurry is completely quickly molded at low temperature, remove the mold to obtain a stent blank;
[0011] S4, placing the scaffold blank into a freeze dryer and freeze drying for 48 hours, then taking it out to obtain a freeze-dried scaffold blank;
[0012] S5. The freeze-dried scaffold blank is placed in a muffle furnace for sintering to complete the preparation of the calcined natural copper / β-tricalcium phosphate scaffold.
[0013] The present invention is further configured as follows: the preparation of the calcined natural copper water extract in step S1 is performed by a reflux extraction method, and the specific preparation process is as follows: first, 20 g of calcined natural copper pieces are added with 100 mL of ultrapure water, and reflux extraction is performed for 120 min, and then the filtrate is filtered using filter paper to obtain a filtrate, and then the filtrate is concentrated and passed through a 0.45 μm microporous filter membrane, and the volume is fixed to 2 mL using ultrapure water to obtain the calcined natural copper water extract.
[0014] The present invention is further configured as follows: 1 mL of the calcined natural copper water extract is equivalent to 10 g of the original medicine, and the storage condition is to store it at 4° C. for use.
[0015] The present invention is further configured as follows: the preparation process of the PVA solution in step S2 is: weigh 921.67 mg of PVA powder, add 10 mL of ultrapure water boiled to near boiling point and stir evenly to prepare the PVA solution.
[0016] The present invention is further configured as follows: the concentration of the PVA solution is 92.167 mg / mL.
[0017] The present invention is further configured as follows: the process of placing the bracket blank into the muffle furnace for sintering in step S5 is: first, the muffle furnace heating rate is set to 2°C / min, the sintering temperature is set to 1150°C, and after being kept warm for 360 minutes, the temperature is naturally cooled to room temperature to obtain the prepared calcined natural copper / β-tricalcium phosphate bracket.
[0018] The present invention also provides a method for preparing a calcined natural copper / β-tricalcium phosphate scaffold and its application in promoting angiogenesis in vitro.
[0019] The present invention also provides a method for preparing a calcined natural copper / β-tricalcium phosphate scaffold and its application in promoting bone defect repair.
[0020] In summary, the present invention has the following beneficial effects:
[0021] 1. The present invention prepares a safe and effective calcined natural copper bone repair scaffold, which can be implanted in situ to provide mechanical support for the load-bearing bone defect, broadens the calcined natural copper drug delivery method, and has good performance. It can promote the angiogenesis of HUVECs and then promote osteogenesis. In the process of bone repair, the Notch-VEGF signaling pathway is used to upregulate the expression of Notch1, promote the expression of VEGF, BMP2, etc., and promote the osteogenesis-angiogenesis coupling in the process of bone defect repair, thereby achieving the therapeutic effect of accelerating bone defect repair;
[0022] 2. The present invention uses 3D printing freeze casting technology for the first time to prepare a bone repair scaffold loaded with traditional Chinese medicine calcined natural copper / β-tricalcium phosphate, which broadens the use of calcined natural copper, improves the mechanical strength of the scaffold, improves the shortcomings of insufficient mechanical properties of traditional ceramic materials, and broadens the application options of medical ceramic materials in clinical orthopedics;
[0023] 3. This paper starts from the perspective of osteogenesis-angiogenesis coupling in the process of bone defect repair and further explains that calcined natural copper can promote the interaction between angiogenesis and osteogenesis in the process of bone defect repair based on the Notch-VEGF signaling pathway, thereby accelerating the bone defect repair process;
[0024] 4. The calcined natural copper / β-tricalcium phosphate bone repair scaffold prepared by the present invention has the ability to promote the repair of bone defects, has good physical and chemical properties, good biological safety, can promote the osteogenesis-angiogenesis coupling process, thereby accelerating the repair process of bone defects, and is expected to become another choice for clinical orthopedic treatment of bone defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a flow chart of the preparation of the bone repair scaffold in Example 1 of the present invention;
[0026] Figure 2 This is an appearance diagram of the bone repair scaffold in Example 1 of the present invention;
[0027] Figure 3 is the XRD pattern of the stent in Example 1 of the present invention;
[0028] Figure 4 FT-IR infrared spectra of three groups of scaffold materials in Example 1 of the present invention;
[0029] Figure 5 is a surface morphology diagram of the stent in Example 1 of the present invention;
[0030] Figure 6 is a graph showing the mechanical strength test results of each group of brackets at different sintering temperatures in Example 1 of the present invention;
[0031] Figure 7 This is a graph showing the mechanical strength test results of the stent with different drug dosages in Example 1 of the present invention;
[0032] Figure 8 is a graph showing the determination of the porosity of the stent in Example 1 of the present invention;
[0033] Fig. 9 is a graph showing pH changes during the degradation of the stent in Example 1 of the present invention;
[0034] Fig.10 is a graph of cumulative degradation rates during the degradation of the stent in Example 1 of the present invention;
[0035] Fig.11 This is a diagram showing the results of a hemolysis experiment in Example 1 of the present invention;
[0036] Fig.12 This is a diagram of an in vitro hemolysis experiment in Example 1 of the present invention;
[0037] Fig.13 This is a graph showing the results of HUVECs proliferation-toxicity study 24 hours after administration in Example 2 of the present invention;
[0038] Fig.14 This is a diagram showing the live and dead cell staining results of HUVECs in Example 2 of the present invention;
[0039] Fig.15 is a diagram showing the adhesion of HUVECs on each group of scaffolds in Example 2 of the present invention;
[0040] Fig.16 This is a diagram showing the wound healing status of HUVECs in each group after administration at different time periods in Example 2 of the present invention;
[0041] Fig.17 This is a graph showing the scratch healing rate of HUVECs in each group after administration at different time points in Example 2 of the present invention;
[0042] Fig.18 This is a diagram showing the migration of HUVECs in the Transwell chamber 24 hours after administration in Example 2 of the present invention;
[0043] Fig.19 This is a quantitative statistical result diagram of HUVECs transmembrane cells 24 hours after administration in Example 2 of the present invention;
[0044] Fig. 20 is the result of the biochemical analysis of New Zealand white rabbit serum in Example 3 of the present invention;
[0045] Fig.21 This is a graph showing the determination of the thymus index after 4, 8, and 12 weeks of stent implantation in Example 3 of the present invention;
[0046] Fig. 22 The spleen index is measured 4, 8, and 12 weeks after stent implantation in Example 3 of the present invention;
[0047] Fig.23 This is the HE staining result of the organs of New Zealand white rabbits in Example 3 of the present invention;
[0048] Fig.24 is the Micro-CT three-dimensional reconstruction image in Example 3 of the present invention;
[0049] Fig.25 This is a diagram of the BV analysis results in Example 3 of the present invention;
[0050] Fig.26 is a diagram of the BV / TV analysis results in Example 3 of the present invention;
[0051] Fig. 27 This is a diagram of the Tb.Sp analysis results in Example 3 of the present invention;
[0052] Fig.28 This is the HE staining result of the bone defect at 4, 8 and 12 weeks in Example 3 of the present invention;
[0053] Fig.29 This is a quantitative analysis result diagram of HE staining at bone defects at 4, 8, and 12 weeks in Example 3 of the present invention;
[0054] Fig.30 This is a graph showing the analysis results of bone biochemistry related indicators in Example 3 of the present invention;
[0055] Fig.31 This is a graph showing the immunohistochemistry results of Notch1, VEGF, and BMP-2 in each group 4 weeks after surgery in Example 3 of the present invention. DETAILED DESCRIPTION
[0056] The following is combined with Figure 1-31 The present invention is described in further detail.
[0057] Example 1: A method for preparing a calcined native copper / β-tricalcium phosphate scaffold, comprising the following steps:
[0058] S1. First, take 20g of calcined natural copper slices and add 100mL of ultrapure water, reflux extraction for 120min, then filter with filter paper to obtain the filtrate, then concentrate the filtrate and pass it through a 0.45μm microporous filter membrane, and use ultrapure water to make the volume to 2mL to obtain the calcined natural copper water extract.
[0059] Among them, 1mL of the calcined natural copper water extract is equivalent to 10g of the original drug, which is stored in a 4°C refrigerator for use. At the same time, ICP-AES is used to determine the contents of Fe, S, Ca, Mg and other elements in the calcined natural copper water extract. According to the ICP-AES measurement results, the Fe element content in the calcined natural copper water extract is the highest, reaching 43.30mg / mL, followed by S element, which is 26.60mg / mL, Ca element content is 2.35mg / mL, and Mg element content is 1.80mg / mL.
[0060] S2. Take a certain amount of β-TCP added with the calcined natural copper water extract, and mix the PVA solution, glycerol and ultrapure water thoroughly and evenly, remove bubbles, and obtain a uniform slurry.
[0061] In this embodiment, the PVA solution is prepared in advance. The preparation process of the PVA solution is as follows: weigh 921.67 mg of PVA powder, add 10 mL of ultrapure water boiled to near boiling point and stir evenly to prepare a PVA solution, wherein the concentration of the PVA solution is 92.167 mg / mL; the formula ratio of each group of scaffolds is shown in Table 1:
[0062] Table 1 Parameters of different groups of scaffold formulations
[0063] Element Material β-TCP LPPD / β-TCP HPPD / β-TCP 1 β-TCP(g) 3.07 3.07 3.07 2 PVA solution (mL) 1.00 1.00 1.00 3 Glycerol (mg) 300 300 300 4 PPD(mL) --- 2.23 4.46 5 Ultrapure water (mL) 6.23 4.00 1.77
[0064] S3, using a syringe to quickly add the uniform slurry on a plate tank pre-cooled at -30°C into the stent mold, and after the slurry is quickly molded at low temperature, remove the stent mold to obtain a stent blank;
[0065] S4, placing the scaffold blank into a freeze dryer and freeze drying for 48 hours, then taking it out to obtain a freeze-dried scaffold blank;
[0066] S5. The heating rate of the muffle furnace is set to 2°C / min, and the sintering temperature is set to 1150°C. After keeping warm for 360 minutes, the temperature is naturally cooled to room temperature to complete the preparation of the calcined natural copper / β-tricalcium phosphate scaffold.
[0067] Preparation process of bone repair scaffold Figure 1 As shown, the prepared bone repair scaffold is as Figure 2 As shown in the figure, it can be seen that the shape of the prepared stent is generally regular and cylindrical. Compared with before sintering, each group of stents after sintering has different degrees of lateral, longitudinal and mass shrinkage. The β-TCP stent group not loaded with Chinese herbal medicine calcined natural copper extract is pure white, the base color of β-TCP, and the LPPD / β-TCP stent group and HPPD / β-TCP stent group loaded with different doses of Chinese herbal medicine calcined natural copper extract are dark red of different color depths.
[0068] In this embodiment, the sintered stents were subjected to XRD analysis, FT-IR analysis, surface morphology observation, mechanical strength measurement, shrinkage measurement, porosity measurement, degradation performance investigation and in vitro hemolysis performance evaluation; wherein the stent XRD analysis was performed using Cu target Kα radiation, λ = 0.15405nm, tube voltage 40KV, current 30mA, scanning range 10°-70° for analysis; the XRD spectra of the three groups of stent materials are as follows Figure 3 As shown in the figure, it can be seen that the main phase of each group of scaffolds is β-TCP phase. Among them, the LPPD / β-TCP and HPPD / β-TCP group scaffold samples also contain calcined natural copper phase, which is consistent with the incorporation of calcined natural copper liquid phase, indicating that the β-TCP in the scaffold material successfully loads the calcined natural copper component of traditional Chinese medicine.
[0069] FT-IR analysis is to examine the functional group structure of the scaffold material and whether the phase of the scaffold material has changed. Specifically, the samples are tested using a Nicolet iS5 Fourier transform infrared spectrometer with a wave number range of 400 cm-1 to 4000 cm-1, 16 scans, a resolution of 4 cm-1, and a measurement temperature of room temperature with an ambient humidity of <40%. The FT-IR infrared spectra of the three groups of scaffold materials are shown in the figure below. Figure 4 As shown, according to prior art reports, 550cm-1, 603cm-1, 941cm-1, 1021cm-1 and 1120cm-1 are the main infrared characteristic frequencies of β-TCP. In the three spectra, the two characteristic peaks of 550cm-1 and 1120cm-1 are the unique diffraction peaks of β-TCP. There are obvious characteristic peaks of PO43- at 603cm-1, 941cm-1 and 1021cm-1. 603-550cm-1 is the bending vibration peak of the OPO bond of the PO43- ion. The stretching vibration peak of the PO bond is at 1120-941cm-1, which is consistent with β-TCP. FT-IR analysis shows that the PVA solution is completely thermally decomposed during the sintering process without obvious residue; the scaffold does not undergo phase change at the sintering temperature; no chemical reaction occurs during the drug loading process to produce new functional group structures; combined with the experimental results of the above-mentioned scaffold XRD analysis, the preparation of the material in the experiment is a physical synthesis, and the chemical properties of the base material β-TCP and the effective ingredients of the traditional Chinese medicine calcined natural copper are not changed. The preparation method is safe, reasonable and effective.
[0070] The morphology of the stent was observed by scanning electron microscopy (SEM) of HITACHIS-4800. The acceleration voltage was 10 kV and the appropriate scanning magnification was selected. The morphology of the stent detected by SEM was as follows: Figure 5 As shown, both the top view and the side view of the cylindrical scaffold show that the scaffold has a microporous structure; the pore size ranges from 2μm to 40μm, which is conducive to the passage of cells.
[0071] Mechanical strength determination is to use compression method to determine whether the prepared scaffold has the mechanical strength matching that of bone. The bone repair scaffolds of each group prepared at sintering temperature of 1050℃, 1100℃ and 1150℃ and kept warm for 360min were placed on the test platform of biomechanical electric servo test system for mechanical strength determination. Before the determination of each scaffold, the diameter of its cross-sectional circular surface under force was measured with a digital display vernier caliper. Three scaffolds were measured in parallel in each group, and the compression speed was set to 1.0mm / min. At the same time, the blank β-TCP group and the LPPD / β-TCP group and HPPD / β-TCP group loaded with different amounts of calcined natural copper water extract were subjected to mechanical strength determination under the same test conditions at 1150℃ and kept warm for 360min. The calculation formula is as follows:
[0072]
[0073] Where P is the compressive strength (MPa), F is the maximum effective breaking load (N), S is the compressed area (m 2 ), Φ is the diameter of the cross-section circle of the stent (m), and Π is the pi; the mechanical strength test results of the stent at three different sintering temperatures are shown in Figure 6 ( n=3; *p<0.01; **p<0.0001). As shown in the data, with the increase of sintering temperature, the mechanical strength of each group of scaffolds increased significantly to varying degrees regardless of whether β-TCP was loaded with drugs or not. When the sintering temperature reached 1150℃, the mechanical strength was greatly improved. Under the same sintering procedure, the mechanical strength of the scaffold after β-TCP loading increased, which is consistent with the existing literature reports that the mechanical strength of ceramic materials increased after loading metal elements. The insulation time was maintained at 360min. Within the sintering temperature range of 1050℃ to 1150℃, the mechanical strength of the scaffold was positively correlated with the sintering temperature, with a significant difference (p<0.05).
[0074] Under the set process conditions of 2℃ / min heating to 1150℃ sintering temperature and 360min holding time, the effect of the amount of calcined natural copper water extract on the mechanical strength of the scaffold was investigated. Figure 7 As shown, ( n=3; *p<0.05). Compared with the blank β-TCP group without drug loading, the mechanical strength of the scaffolds in the LPPD / β-TCP and HPPD / β-TCP groups was significantly increased (p<0.05). Moreover, within a certain dosage range, the mechanical strength of the scaffolds was positively correlated with the dosage of the calcined natural copper aqueous extract.
[0075] Appropriate mechanical strength is particularly important for filling and repairing bone defects in load-bearing bones. According to the mechanical strength measurement results, in this embodiment, a heating rate of 2°C / min, a sintering temperature of 1150°C, a heat preservation time of 360 minutes, and a temperature drop to room temperature under natural conditions are specifically selected as the sintering process for the scaffold.
[0076] The shrinkage rate is measured by using an electronic balance and a digital vernier caliper to measure the specific values of each corresponding bracket. The measurement formula is as follows:
[0077]
[0078]
[0079] Where m is the mass, Φ is the diameter, h is the height, the volume of the scaffold is V, which is recorded as m1, Φ1, h1 and V1 before sintering and m2, Φ2, h2 and V2 after sintering. m is the mass shrinkage rate, ω v Volume shrinkage, ω x is the transverse shrinkage rate, ω y is the longitudinal shrinkage rate.
[0080] The mass and volume of different scaffolds shrink to varying degrees after sintering, as shown in Table 2:
[0081] Table 2 Treatment results of shrinkage rates in different stent groups
[0082]
[0083] Among them, *p<0.05, compared with the β-TCP group; #p<0.05, compared with the LPPD / β-TCP group.
[0084] The porosity is measured by the Archimedes drainage method. The specific porosity calculation formula is as follows:
[0085]
[0086] The weight of the dry support is W. S , fill the pycnometer with ethanol (95%), weigh it and record it as W1, add the dry bracket to the pycnometer, use a vacuum pump to pump ethanol into the porous part of the bracket under pressure until there are no bubbles in the pycnometer, add ethanol to fill the pycnometer, weigh it and record it as W2, take out the bracket, weigh the pycnometer and the weight of the remaining ethanol in the bottle and record it as W3, ρ e is the density of ethanol.
[0087] The porosity of the scaffold was measured as follows: Figure 8 As shown ( n=3), and the Archimedean drainage method showed that the average porosity of the scaffolds in the β-TCP group was 74.421%, the average porosity of the scaffolds in the LPPD / β-TCP group was 73.428%, and the average porosity of the scaffolds in the HPPD / β-TCP group was 74.245%. The microscopic porosity of the scaffolds in each group was good, distributed in a reasonable range of 68%-82%. There was no significant difference in porosity between the groups before and after drug loading (P=0.6901, 0.9562); at the same time, there was no significant difference between the drug-loaded groups (P=0.7911), and there was no significant change in porosity before and after drug loading, indicating that drug-loaded PPD had no significant effect on the porosity of the β-TCP scaffold, and the scaffold still had good microporous characteristics. Micropores can also be used as a method to control the resorption and dissolution rate. The larger the micropores, the greater the degradation rate. At the same time, increasing the number of micropores can achieve a larger specific surface area, which is also essential for bone conduction in bone regeneration.
[0088] The purpose of investigating the degradation performance is that the scaffold needs to have a certain degradation rate so that it can be gradually replaced during the growth of new tissue. The scaffold implanted in the bone defect is mainly in contact with tissue fluid and body fluid, so hydrolysis is one of its most important degradation mechanisms. In this embodiment, the cumulative degradation rate of the scaffold and the change in pH value of the degradation solution are mainly investigated.
[0089] Each group of scaffolds was dried and weighed, and added to a centrifuge tube containing 5.0 mL of PBS (pH 7.2-7.4) solution. The centrifuge tube was placed in a water bath constant temperature oscillator and oscillated at 37°C and 160 r / min. The scaffolds were taken out at fixed intervals, dried in a 105°C constant temperature drying oven, and weighed. The cumulative degradation rate of each group of scaffolds was calculated as follows:
[0090]
[0091] Among them, m0 is the dry weight of each group of brackets, m x It is the weight after drying in a drying oven; the pH value in the scaffold degradation solution is measured by using a pH meter.
[0092] The pH changes during the scaffold degradation process are as follows Fig. 9 ( n=3), it can be seen from the results that the pH change of the solvent has almost no effect on the degradation process of the scaffold. Within 5 weeks of degradation, the pH value is maintained within the normal pH range of the PBS buffer. The cumulative degradation rate during the degradation process of the scaffold is as follows Fig.10 ( n=3), as shown in the results, as time goes by, the degradation rate of the stent also increases, and the β-tricalcium phosphate group stent degrades the fastest, which is also consistent with the literature reports of the prior art. By the third week, the blank β-TCP group stent without Chinese medicine calcined natural copper water extract degrades significantly faster than the group of stents loaded with Chinese medicine calcined natural copper water extract, and the gap becomes more and more obvious as time goes by. At the same time, this also shows that the mechanical strength of the β-tricalcium phosphate loaded with metal element Chinese medicine is improved after freeze casting, which leads to a slow degradation rate, which is confirmed by the experimental results.
[0093] The in vitro hemolytic performance evaluation was performed by taking 20 mg of the scaffold materials from different groups and dissolving them in 500 μL 0.01 mol / L PBS (pH 7.2-7.4), using ultrapure water as the positive control and 0.01 mol / L PBS (pH 7.2-7.4) as the negative control. After each group of sample tubes was placed in a 37°C water bath for 30 min, 500 μL of 2% red blood cell suspension was added to each tube and mixed. After each group of sample tubes was placed in a 37°C water bath for 60 min and centrifuged at 1000 r / min for 10 min, the supernatant was transferred into a 96-well cell culture plate (80 μL / well), and the absorbance (optical density, OD) value of each group was measured at a wavelength of 540 nm. The formula for calculating the hemolysis rate (Hemolysis rate, HR) is as follows:
[0094]
[0095] Hemolysis rate is an important indicator for biocompatibility evaluation. The results of in vitro hemolysis test are as follows: Fig.11 (A: positive group; B: negative group; C: β-TCP group; D: LPPD / β-TCP group; E: HPPD / β-TCP group) and Fig.12 As shown ( n=3), the average hemolysis rate of the three groups of stent materials was between 2.6% and 2.8%, and the hemolysis rate was evaluated according to ISO10993-4:2002 standard: a hemolysis rate ≤5% indicated that the material met the hemolysis requirements of medical biomaterials, and a hemolysis rate >5% did not meet the requirements. The results showed that the stents prepared in this study met the hemolysis requirements of medical biomaterials and had good biocompatibility.
[0096] Conclusion: In this embodiment, a bone repair scaffold of a Chinese medicine calcined natural copper water extract composite β-tricalcium phosphate bioceramic material was prepared by 3D printing freeze casting technology, and the preparation process was investigated from the sintering temperature, the main factor affecting the mechanical strength, to determine the preparation and sintering process of the scaffold, and then the composition of the scaffold before and after sintering, the shrinkage rate before and after sintering, the mechanical strength, the microscopic surface morphology of the scaffold, the porosity, the degradation performance, the in vitro hemolysis performance and other physical and chemical properties were investigated and characterized; the experimental results show that the scaffold preparation and sintering process of this study is feasible, the scaffold is formed, the prepared composite scaffold has good physical and chemical properties, the chemical composition of the scaffold does not change before and after sintering, the scaffold shrinks after sintering, which is beneficial to improve the mechanical strength of the scaffold, the scaffold after sintering has a certain mechanical strength, and can play a supporting role at the implanted bone defect site, the scaffold surface is uneven, which is conducive to cell adhesion, and the scaffold surface is distributed with numerous microscopic pores, so that the scaffold has a certain porosity, which is conducive to the passage and aggregation of cells, promotes angiogenesis, degradation investigation, and in vitro hemolysis experiment prove that the scaffold material has good biocompatibility and meets the implantation requirements of biomedical materials.
[0097] Example 2: Experimental study on promoting angiogenesis in vitro using a calcined natural copper / β-tricalcium phosphate scaffold
[0098] This embodiment includes HUVECs proliferation-toxicity experiment, HUVECs adhesion experiment, HUVECs scratch healing experiment and HUVECs Transwell chamber experiment; wherein the HUVECs proliferation-toxicity experiment is to soak each group of scaffolds in a sterile test tube containing fresh complete cell culture medium (DMEM High Glucose cell culture medium + 10% fetal bovine serum by volume) according to an extraction ratio of 10.0 mg / mL, and then seal and place in a constant temperature water bath oscillator at 37°C and 150r / min (48±0.5)h, take the extract and filter (0.22μm filter) and store at 4°C for standby use, thereby completing the preparation of the scaffold extract.
[0099] In this embodiment, the experimental grouping was divided into a blank group, a control group, and different scaffold extract groups; the filtered extract was diluted 10 1 times, 10 3 Times and 10 5 times, as experimental dosing groups with different concentrations; HUVECs with good growth conditions were counted and diluted to make the cell suspension concentration 8.0×10 4cells / mL, inoculated in a 96-well cell culture plate, the inoculation volume was 100 μL / well, and no cell suspension was added to the blank group; the cell culture plate was placed in a cell culture incubator at 37°C and a CO2 volume fraction of 5% overnight until the cells were completely attached to the wall; different groups and concentrations of scaffold extracts (except the blank group and the control group) were added, and the blank group and the control group were added with an equal amount of DMEM high-glucose complete medium containing 10% fetal bovine serum, and 4 replicates were set for each group; 24 hours after administration, 10 μL of CCK-8 cytotoxicity detection reagent was added to each well in the clean bench, and after slight shaking, it was continued to be incubated for 60 minutes in a cell culture incubator at 37°C and a CO2 volume fraction of 5%, and the culture plate was taken out, and the absorbance value (OD) of each well was recorded at a wavelength of 450nm using an enzyme marker; the formula for calculating the relative growth rate (Relative Growth Rate, RGR) of the cells is as follows:
[0100]
[0101] The cytotoxicity ratings are shown in Table 3:
[0102] Table 3 Cytotoxicity grading evaluation table
[0103] RGR value significance grade >90% No cytotoxicity Level 0 =60~90% Mild cytotoxicity Level I =30~59% Moderate cytotoxicity Level II ≤30% Severe cytotoxicity Grade III
[0104] After 24 hours of cell culture, HUVECs were stained using the Calcein / PI cell viability and cytotoxicity detection kit to evaluate the effect of the scaffold extract on cell morphology; the stained cells were observed using an inverted biological microscope to evaluate the morphology of cell survival.
[0105] like Fig.13 ( n=4; *p<0.05; **p<0.01; ***p<0.0001), as shown in the above data, within the dosage concentration range, the cells can grow normally. According to the cytotoxicity evaluation standard, the RGR value of each group is >90%, belonging to level 0, and has no cytotoxicity; indicating that both the blank β-TCP scaffold and the β-TCP scaffold loaded with natural copper of traditional Chinese medicine have no cytotoxicity to HUVECs, and the scaffold is safe and reliable.
[0106] like Fig.14 As shown, after the cells were cultured in the incubator for 24 hours, the culture plates were taken out for staining and then observed under a microscope. The HUVECs in each group survived well, had normal cell morphology, and grew normally, which was consistent with the aforementioned CCK-8 results.
[0107] In addition, it can be seen from the results that in the concentration used in this embodiment, when the dilution factor is 10 3When , the scaffold extract has the best effect on promoting HUVECs proliferation. Compared with the control group, the PPD-loaded scaffold can significantly promote the proliferation of HUVECs. At the same dilution multiple, compared with the β-TCP group, the PPD-loaded β-TCP scaffold can significantly promote the proliferation of HUVECs, and the HPPD / β-TCP group has a better proliferation-promoting effect than the LPPD / β-TCP group. Therefore, this embodiment prefers the concentration under this dilution multiple as the HUVECs dosing concentration.
[0108] The HUVECs adhesion experiment was conducted by using a HITACHI Regulus 8100 scanning electron microscope to observe the growth and adhesion of HUVECs on the scaffold. HUVECs with good growth status were counted and counted at 2×10 6 cells / well were inoculated in a 48-well plate. After the scaffolds were cultured in cell growth medium for 24 h, they were taken out, washed twice with PBS, and stored in electron microscope fixative at 4°C. After dehydration, drying, and gold spraying, they were placed in a scanning electron microscope for photography, and the appropriate magnification and field of view were selected.
[0109] The experimental results are as follows Fig.15 As shown, it can be seen from the electron microscope scanning image that there are many irregular pores and depressions on the surface of the scaffold, which is not only conducive to the passage of cells, but also provides the possibility for cell attachment. The SEM characterization results show that HUVECs can form good adhesion on each group of scaffolds.
[0110] The steps of the HUVECs scratch healing experiment are as follows: the experimental groups are blank control group (Control), β-TCP group, LPPD / β-TCP group and HPPD / β-TCP group; take a 6-well plate and use a marker pen to evenly draw lines on the back of the plate with a ruler, cross the holes horizontally, and cross 3 lines in each hole; take HUVECs in good growth state and in the logarithmic growth phase, digest them with trypsin, add 10% DMEM full culture medium after centrifugation, blow and evenly make a single cell suspension and inoculate it into a 6-well plate, the cell inoculation density is 6.5×105cells / well, add 2mL of culture medium to each well, and place the cell culture plate in a cell culture incubator at 37°C and 5% CO2 overnight until the cells are completely attached to the wall and spread. About 90% of the bottom of the plate formed a single cell layer. A 200 μL yellow pipette tip was used to scratch the fused single cell layer perpendicular to the horizontal line on the back of the plate with a ruler. The pipette tip was kept vertical, and 3 scratches were made in each well. The cells were gently washed 3 times with PBS to remove the cells that were not attached to the wall and scratched. The blank control group was added with 10% DMEM high-glucose complete medium, and the drug-treated groups were added with scaffold extracts of different groups. 2 mL of solution was added to each well and incubated in a cell culture incubator at 37°C and a CO2 volume fraction of 5%. After 0h, 12h, and 24h of drug administration, the culture plate was placed under an inverted biological microscope (50×) and fixed positions were taken to take pictures using the software ZEN to ensure that the positions for taking pictures at different times were consistent. Four fixed positions were randomly taken for each group to take pictures, and the scratch area (S) was measured using Image J software. The scratch area at 0h was recorded as S0, and the scratch area at a fixed time point was recorded as St. The formula for calculating the scratch healing rate (Wound healing rate) of HUVECs in each group is as follows:
[0111]
[0112] The results of HUVECs scratch healing experiment are as follows Fig.16 and Fig.17 (( n=4; *p<0.05; **p<0.01; ***p<0.005); 12h after administration, compared with the Control group, both the LPPD / β-TCP group and the HPPD / β-TCP group could significantly promote the healing of HUVECs scratches; compared with the β-TCP group, both the LPPD / β-TCP group and the HPPD / β-TCP group loaded with calcined natural copper could significantly promote the healing of HUVECs scratches, and there was no significant difference between the LPPD / β-TCP group and the HPPD / β-TCP group (P=0.7022), but within a certain range, the trend of increasing the healing rate of scratches was similar to that of the added amount of calcined natural copper water extract. Positive correlation. 24h after administration, compared with the Control group, both the LPPD / β-TCP group and the HPPD / β-TCP group could significantly promote the healing of HUVECs scratches. Compared with the β-TCP group, the HPPD / β-TCP group loaded with calcined natural copper could significantly promote the healing of HUVECs scratches. Although there was no significant difference in the LPPD / β-TCP group (P=0.0704), the scratch healing rate showed an increasing trend. There was no significant difference between the LPPD / β-TCP group and the HPPD / β-TCP group (P=0.5826), but within a certain range, the increasing trend of the scratch healing rate was positively correlated with the dosage of the calcined natural copper water extract.
[0113] HUVECs Transwell chamber experiment: The experimental grouping and drug concentration were the same as the HUVECs scratch healing experiment in this chapter. HUVECs in good growth state and in the logarithmic growth phase were digested with trypsin, centrifuged, and resuspended in DMEM high-glucose basal medium (without double antibody) and counted. Then, the medium was diluted to 5×10 5 cells / mL of cell suspension for later use. In the lower chamber of the Transwell culture plate, add 10% DMEM high-glucose complete medium to the blank control group, and add different groups of scaffold extracts to the drug-treated group, with a volume of 600 μL / well. Add the above cell suspension to the Transwell chamber (chamber filter membrane pore size 8.0 μm), add a volume of 100 μL / well (5×10 4 cells) (be careful to prevent bubbles); incubate the Transwell culture plate in a cell culture incubator at 37°C and 5% CO2 volume fraction for 24 hours, take out the Transwell chamber in the Transwell culture plate, wash it three times with PBS, soak the chamber in 4% paraformaldehyde for 20 minutes, take it out and wash it three times with PBS, soak the chamber in 0.1% crystal violet aqueous solution for 20 minutes, gently wipe off the cells in the upper chamber of the Transwell with a cotton swab, wash it three times with PBS, and take pictures and count the cells that migrated to the lower chamber at four random 200× magnification fields under an inverted biological microscope.
[0114] The results of the Transwell chamber experiment are as follows Fig.18 (Migration of HUVECs in Transwell chamber 24 hours after drug administration) (200×) and Fig.19 As shown (quantitative statistical results of HUVECs transmembrane cells 24 hours after administration) ( n=4; *p<0.05; **p<0.01; ****p<0.0001); After administration, the number of HUVECs penetrating the membrane increased significantly, and the β-TCP scaffold loaded with calcined natural copper water extract promoted the further increase of HUVECs migration, which was consistent with the aforementioned scratch healing experiment, indicating that the scaffold had a good ability to promote HUVECs migration and healing, which was beneficial to the aggregation of HUVECs and the rapid generation of blood vessels, thereby accelerating bone regeneration.
[0115] Conclusion: In this example, HUVECs were used as experimental objects to investigate the effect of the prepared scaffold on HUVECs angiogenesis in vitro. Experimental studies have shown that the prepared scaffold is non-toxic to cells and can promote the proliferation and growth of HUVECs. After loading the Chinese medicine calcined natural copper water extract, the scaffold further enhances the proliferation of HUVECs. Within a certain dose range, the proliferation of HUVECs is positively correlated with the drug loading dose; at the same time, SEM images show that with the help of the non-planar microscopic morphology of the scaffold surface, HUVECs can form good attachment and spread growth on the scaffold, and can maintain a certain cell morphology. Scratch experiments and Transwell chamber experiments show that β-tricalcium phosphate scaffolds can promote the migration of HUVECs, which is consistent with the reported β-tricalcium phosphate can be used for bone repair. In addition, after loading the Chinese medicine calcined natural copper water extract, the scaffold further enhances the migration of HUVECs, and within a certain dose range, the number of cell migration movements is positively correlated with the β-tricalcium phosphate drug loading dose, which further indicates that the scaffold loaded with Chinese medicine has better angiogenesis ability.
[0116] Example 3: Experimental study on the effect of a calcined natural copper / β-tricalcium phosphate scaffold on promoting bone defect repair
[0117] This embodiment includes the construction of an animal model and stent implantation, observation of the general condition of experimental animals, serum biochemical analysis, determination of thymus and spleen indexes, evaluation of organ safety, Micro-CT scanning analysis, bone tissue morphology analysis, analysis of bone biochemical related indicators and detection of osteogenic-angiogenic related indicators; wherein the construction of the animal model and stent implantation are to randomly divide 36 New Zealand white rabbits into the following four groups: a blank control group in which no stent is implanted in the bone defect; an experimental group in which β-TCP stents, LPPD / β-TCP stents containing 5% PPD and HPPD / β-TCP stents containing 10% PPD are implanted in the bone defect; all stents are sterilized by high-pressure steam and ultraviolet sterilization in advance, and animal experiments are carried out after all animals are adaptively raised, and all New Zealand white rabbits are raised in single cages throughout the entire cycle of the animal experiment.
[0118] 12h before surgery, New Zealand rabbits were fasted but not watered. After measuring their weight, 75% medical alcohol was used to disinfect the ear vein of New Zealand rabbits. After 3% sodium pentobarbital (30mg / kg) was slowly injected for anesthesia, the rabbits were fixed on the operating table in a lateral supine position to keep their breathing unobstructed. The surgical site and surrounding rabbit hair were removed with a shaver, a tourniquet was tied, and the rabbits were disinfected with iodine and 75% medical alcohol. A 3cm long incision was made at the distal end of the right femur using sterile surgical instruments. The muscle layer was dissected with surgical instruments to expose the bone platform. A medical electric drill was used to drill vertically downward at the distal end of the femur. A cylindrical bone defect with a height of 7mm and a diameter of 8mm was made using a grinding drill. The surgical site was flushed with sodium chloride injection while drilling. The blank group was sutured directly after the bone defect was prepared. The other groups were implanted with a pre-prepared stent, and the muscles, fascia and skin were sutured. The rabbits were placed on an electric blanket and waited for natural awakening. After observation without abnormality, they were put back in the cage for feeding and eating and drinking normally. Sodium penicillin was injected intramuscularly to prevent wound infection, with a dose of 4×105U / animal / day, once a day, for 3 consecutive days. The animals were killed in batches (3 animals per group, 12 animals per batch) at 4, 8, and 12 weeks after surgery to investigate the repair effect and bone repair mechanism of the bone defect.
[0119] The general condition of the experimental animals was observed from the day of surgery to the day of sacrifice and sampling. The daily free growth of the New Zealand white rabbits was observed every day, such as the animal's mental state, wound healing, limb activity, defecation, food intake, hair changes, etc. If there were unexpected situations such as wound rupture or infection, timely debridement was required, and drug treatment was given when necessary. The weight of the New Zealand white rabbits was measured and recorded regularly every week. The New Zealand white rabbits were dissected after sacrifice, and the femur specimens were freed to observe the general morphology and structure of the femur specimens and the growth of the bones after scaffold treatment.
[0120] During the entire experimental period, the New Zealand white rabbits were in good condition, with normal diet and activity, shiny fur, and no significant differences in animal behavior observations among the groups; the wound sutures healed well, the implants did not fall out, there was no foreign body reaction or immune rejection reaction, and the weight of the New Zealand white rabbits in each group showed a normal and stable increasing trend, and there was no significant difference between the groups (p>0.05); the New Zealand white rabbits were killed and dissected, and the femur specimens were freed. The gross morphology and structure of the femur specimens were observed to be normal, and the bone growth was normal.
[0121] Serum biochemical analysis was performed by collecting whole blood samples from New Zealand rabbits 4 weeks after stent implantation using a negative pressure blood collection tube. After being placed at room temperature for 2 hours, the samples were centrifuged at 4000 r / min for 10 minutes, and the supernatant was separated to obtain the serum samples to be tested. The biosafety of stent implantation in New Zealand rabbits was investigated. The indicators investigated
[99] were alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (ALB), globulin (GLOB), albumin / globulin (A / G), total protein (TP), creatinine (CREA) and urea nitrogen (BUN) in serum;
[0122] Serological liver and kidney biochemical index test results showed that the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) of the main liver function indicators of New Zealand white rabbits in each group did not increase significantly, and the levels of albumin (ALB), globulin (GLOB), albumin-globulin ratio (A / G) and total protein (TP) did not decrease significantly; the levels of renal function indicators creatinine (CREA) and blood urea nitrogen (BUN) did not increase significantly, indicating that the stent implantation was safe. Compared with the blank control group without stent implantation, there were no significant differences in the above liver and kidney function indicators in the experimental group (p>0.05), and they were within the normal range. The test results were as follows Fig. 20 As shown ( n=3) Among them: the upper and lower dotted lines are the normal reference range of this laboratory.
[0123] The thymus and spleen indexes were determined by weighing the New Zealand white rabbits 4, 8, and 12 weeks after stent implantation, removing the thymus and spleen of the New Zealand white rabbits after killing them, removing the mucosa around the organs, washing them with physiological saline, absorbing the surface moisture with filter paper, weighing and recording them. The formula for calculating the thymus index and spleen index of the New Zealand white rabbits is as follows:
[0124]
[0125] The immune organ index indicates the immune capacity of an organism to a certain extent. A large immune organ index indicates that New Zealand white rabbits have strong immune capacity; Fig.21 ( n=3) Fig. 22 ( n=3), there was no significant difference in the immune organ indexes (thymus index, spleen index) among the groups at the same time of administration after surgery (p>0.05), indicating that the stent implantation did not damage the body's immunity and the stent had good biological safety.
[0126] The organ safety evaluation is to take the liver, kidney, spleen and thymus of New Zealand white rabbits 4 weeks after stent implantation, and fix part of each tissue in 4% paraformaldehyde universal tissue fixative. After routine embedding, sectioning and HE staining, the organs are examined under a microscope and representative fields are selected for photographing to analyze whether there are any damage and lesions in the organs.
[0127] HE staining results of liver, kidney, spleen and thymus tissue of New Zealand white rabbits are as follows Fig.23 As shown; pathological analysis of the sections showed that the liver lobule structure was normal, the hepatocytes had no obvious degeneration, no necrosis, and no congestion of the hepatic sinusoids; the kidney glomerular structure was clear, the renal tubules were not swollen, there was no edema or local congestion in the renal interstitium, and no inflammatory cell infiltration was observed under the microscope; the spleen capsule was intact and smooth, the structure was intact and clear, the number and size of the splenic bodies in the white pulp and red pulp of the spleen did not change significantly, the number of lymphocytes did not decrease, megakaryocytes were visible in the spleen, and the thymus gland structure was normal, with a thicker cortex and a thinner medulla, and a clear boundary between the cortex and medulla.
[0128] In summary, there were no obvious lesions and toxic reactions in the major organs, indicating that the stent has good biocompatibility in the body, that is, good biosafety in the body.
[0129] Micro-CT scanning analysis is to take bone samples from the bone defect of New Zealand white rabbits 4, 8, and 12 weeks after the implantation of the scaffold, remove the muscles, etc., and fix and preserve them in 4% paraformaldehyde universal tissue fixative. Use Micro-CT to scan the rabbit bone defect samples, with a scanning voltage of 80kV, a current of 313μA, a resolution of 18μm, and a scanning time of 270s to observe the osteogenesis in the bone defect area, select the region of interest (ROI) for threshold segmentation, use the software CTAn to analyze the functional parameters of bone tissue, calculate and measure the three indicators of the selected new bone area, namely, the new bone volume (New Bone Volume, BV), the bone volume fraction (Bone Volume / Tissue Volume, BV / TV), and the trabecular separation (Trabecular Separation, Tb.Sp), and finally use the software CTVol to output a three-dimensional picture of the bone defect area;
[0130] The three-dimensional scan images obtained by Micro-CT software analysis are as follows: Fig.24 The quantitative analysis results of Micro-CT scanning are shown in Fig.25 ( n=3; *p<0.05; ***p<0.001; ****p<0.0001), Fig.26 ( n=3; *p<0.05; ***p<0.001; ****p<0.0001) and Fig. 27 ( n=3; *p<0.05; **p<0.01; ***p<0.001; ****p<0.0001); According to the three-dimensional bone reconstruction and the quantitative analysis results of BV, BV / TV, and Tb.Sp, it is shown that with the extension of postoperative time, the scaffold part begins to degrade, and the new bone in the bone defect of each group shows an increasing trend. The new bone in the scaffold-implanted group is significantly more than that in the blank control group without scaffold implantation, especially in the HPPD / β-TCP group with more calcined natural copper water extract. At the same time after surgery, the bone parameters show a good trend. The experimental results show that the scaffold prepared in this study promotes the repair of bone defects to a certain extent, and the addition of Chinese medicine calcined natural copper can accelerate the bone repair process.
[0131] Bone tissue morphology analysis was performed by cleaning the femur samples of each group after sampling at each time point with physiological saline, fixing them with 4% paraformaldehyde universal tissue fixative, decalcifying them with ethylenediaminetetraacetic acid solution, and placing them in a constant temperature shaker. The solution was changed once every 2-3 days, and the degree of decalcification was observed during the solution change. After decalcification was completed (the needle of a No. 5 syringe could be easily inserted, which was considered to be complete), the samples were embedded in paraffin and sliced. After the slices were stained with hematoxylin-eosin and Masson, the bone tissue morphology was observed under a microscope.
[0132] HE staining and quantitative analysis Fig.28 and Fig.29 ( n=3; **p<0.01; ***p<0.001; ****p<0.0001) as shown: the remaining scaffold material can be seen in the field of vision, which is black (black arrow). Except for the control group without scaffold implantation, the scaffold implantation area shows varying degrees of trabecular hyperplasia, which is tightly arranged to form new bone tissue (red arrow). Osteoblasts and osteoclasts are distributed on the surface of trabeculae. The cell body of osteoblasts (gray arrows) is short columnar or oval, with round nuclei and basophilic cytoplasm; osteoclasts (blue arrows) are multinuclear giant cells formed by the fusion of multiple mononuclear cells. New capillaries can be seen in the gaps and edges of trabeculae (purple arrows), and no obvious inflammatory cell infiltration is observed. As time passed after surgery, osteoblasts gradually increased and osteoclasts decreased, which was beneficial to bone formation. New bone tissue continued to increase. The growth of the scaffold group was significantly greater than that of the blank group without scaffold implantation. The growth of the HPPD / β-TCP group with a high dose of calcined natural copper water extract was the most obvious. The bone tissue was connected into a large area of new bone tissue, and the separation of trabeculae decreased. In addition, bone blood vessels continued to form as time went on.
[0133] The analysis of bone biochemical related indicators is to take serum 4 weeks after surgery, measure the content of major elements such as iron, calcium, and phosphorus, and calculate the calcium-phosphorus product; the animal serum 4 weeks after surgery is subjected to biochemical analysis, and the results are as follows Fig.30 ( n=3; *p<0.05), there was no significant difference in iron and phosphorus, the high-dose HPPD / β-TCP group with drug loading had significantly more calcium, and the calcium-phosphorus product was also significantly higher than that of the other three groups.
[0134] The detection of osteogenic-angiogenic related indicators was carried out by taking paraffin sections of femoral tissues after decalcification from bones sampled 4 weeks later, and performing immunohistochemistry to detect the expression of Notch1 protein, vascular endothelial growth factor (VEGF), and bone morphogenetic protein 2 (BMP-2) in the new bone tissue in the bone defect area. The sections with better staining were selected for observation under a microscope, and appropriate magnifications and representative fields of view were selected to take pictures and analyze the expression.
[0135] Immunohistochemical results of Notch1, VEGF, and BMP-2 Fig.31 As shown in the figure, it can be seen that the scaffold group has more positive area expression (in the red circle), and the expression of each factor is higher than that of the blank group. The scaffold loaded with calcined natural copper water extract upregulates the expression of each factor, and within a certain dosage range, the degree of upregulation is positively correlated with the dosage of calcined natural copper water extract. This indicates that calcined natural copper promotes the osteogenic-angiogenic coupling process through the Notch-VEGF signaling pathway, promotes angiogenesis and bone regeneration, and accelerates bone defect repair.
[0136] Conclusion: This embodiment mainly studies the bone defect repair effect of the scaffold in New Zealand white rabbits from the aspects of in vivo safety, efficacy and mechanism; first, in terms of safety, the New Zealand white rabbits grew well throughout the experimental period, and there was no significant difference in the immune organ index determination among the groups. The pathological analysis of HE section staining of liver, kidney, spleen and thymus tissue showed that the organs of the animals in each group were normal without obvious lesions. The serum biochemical analysis showed that the liver and kidney function indicators of the animals in each group were normal. The above experiments showed that the scaffold had good safety in vivo; in terms of efficacy, the three-dimensional reconstruction image of Micro-CT scanning analysis showed that there was bone tissue regeneration at the bone defect site of each group after surgery, and the bone tissue regeneration in the scaffold implanted group was obvious. The new bone in the scaffold group loaded with Chinese medicine calcined natural copper water extract was more significantly increased. The software was used to perform quantitative analysis of BV, BV / TV and Tb.Sp bone parameters on the Micro-CT scanning results, and the results showed that the bone repair effect: the scaffold group loaded with calcined natural copper water extract was better than the blank β-TCP scaffold group, and the scaffold implanted group was better than the non-scaffold implanted group. Based on osteogenesis-angiogenesis coupling, the mechanism of calcined natural copper composite scaffold in promoting bone defect repair was deeply explored. Immunohistochemical detection of Notch1 protein, VEGF and BMP-2 showed that calcined natural copper upregulated the expression of Notch1, VEGF and BMP-2 through the Notch-VEGF signaling pathway, promoted the coupling process of angiogenesis and osteogenesis, and accelerated the repair of bone defects.
[0137] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a calcined native copper / β-tricalcium phosphate scaffold, characterized by: The following steps are involved: S1, preparing a calcined natural copper aqueous extract and adding it to β-TCP; S2, taking β-TCP added with a quantitative amount of calcined natural copper water extract, and PVA solution, glycerol, and ultrapure water, mixing them evenly, removing bubbles, and obtaining a uniform slurry; S3, using a syringe to quickly add the uniform slurry on a plate tank pre-cooled at -30°C into the stent mold, and after the slurry is completely quickly molded at low temperature, remove the mold to obtain a stent blank; S4, placing the scaffold blank into a freeze dryer and freeze drying for 48 hours, then taking it out to obtain a freeze-dried scaffold blank; S5. The freeze-dried scaffold blank is placed in a muffle furnace for sintering to complete the preparation of the calcined natural copper / β-tricalcium phosphate scaffold.
2. The method for preparing a calcined native copper / β-tricalcium phosphate scaffold according to claim 1, characterized in that: The calcined natural copper aqueous extract is prepared in step S1 by a reflux extraction method, and the specific preparation process is as follows: first, 20 g of calcined natural copper slices are added with 100 mL of ultrapure water, and reflux extraction is performed for 120 min, and then the filtrate is filtered using filter paper to obtain a filtrate, and then the filtrate is concentrated and passed through a 0.45 μm microporous filter membrane, and the volume is fixed to 2 mL using ultrapure water to obtain a calcined natural copper aqueous extract.
3. The method for preparing a calcined natural copper / β-tricalcium phosphate scaffold according to claim 2, characterized in that: 1 mL of the calcined natural copper water extract is equivalent to 10 g of the original drug, and the storage condition is to store it at 4° C. for use.
4. The method for preparing a calcined native copper / β-tricalcium phosphate scaffold according to claim 1, characterized in that: The preparation process of the PVA solution in step S2 is as follows: weigh 921.67 mg of PVA powder, add 10 mL of ultrapure water boiled to near boiling point, stir evenly, and prepare the PVA solution.
5. The method for preparing a calcined native copper / β-tricalcium phosphate scaffold according to claim 4, characterized in that: The concentration of the PVA solution is 92.167 mg / mL.
6. The method for preparing a calcined native copper / β-tricalcium phosphate scaffold according to claim 1, characterized in that: The process of placing the bracket blank into the muffle furnace for sintering in step S5 is as follows: first, the heating rate of the muffle furnace is set to 2°C / min, the sintering temperature is set to 1150°C, and after keeping warm for 360 minutes, the temperature is naturally cooled to room temperature to obtain the prepared calcined natural copper / β-tricalcium phosphate bracket.
7. Use of the preparation method of a calcined natural copper / β-tricalcium phosphate scaffold according to claim 1 in promoting angiogenesis in vitro.
8. Use of the preparation method of a calcined natural copper / β-tricalcium phosphate scaffold according to claim 1 in promoting bone defect repair.
